Genetic Variation and Phylogenetic Analysis of Fungal Pathogens on Native Dendrobium in Lampung using DNA Barcoding - Mahfut Mahfut; Sri Wahyuningsih; Arie Setya Putra (Pandawa Institute, 2026)
Dendrobium is one of the flagship collections of Liwa Botanical Garden, as well as an endemic flora of southern Sumatra that requires conservation. One of the major challenges in its conservation and potential development is the identification of diseases. Molecular approaches employing genetic variation and phylogenetic analyses with DNA barcoding markers can serve as an effective alternative. Genetic variation analysis is required to evaluate the level of intra and interspecific diversity of pathogens, while phylogenetic analysis is necessary to determine the evolutionary relationships among pathogenic fungal species. This study provides insights into the evolutionary patterns and adaptive potential of pathogens to their hosts at the molecular level. A total of 6 out 10 samples showing fungal infection symptoms, such as rust spots, necrosis, and others, were collected. Amplification of two selected samples, D23 and D24, revealed specific bands of approximately 300 bp. Sequence and phylogenetic analyses indicated similarity to isolates of the genera Xylaria and Termitomyces, with sequence lengths ranging from 513 to 671 bp, respectively. Genetic variation analysis through haplotype grouping showed that isolate D23 clustered with the Xylariales group, while isolate D24 clustered with the Termitomyces group. The findings of this study enrich the sequence data of pathogenic fungi, although with a limited success rate, and provide a molecular basis for the accurate conservation of native Dendrobium in the Liwa Botanical Garden through protection against disease infections.